Answer: x = 2 , y = 5
Explanation:
Given:
y = 2x + 1 ............................................ equation 1
3y = 4x + 7 ......................................... equation 2
Solving the system of linear equation by substitution method:
substituting y = 2x + 1 into equation 2 , we have
3(2x+1) = 4x + 7
Expanding , we have :
6x + 3 = 4x + 7
Subtracting 4x from both sides , we have
6x - 4x + 3 = 7
2x + 3 = 7
subtracting 3 from both sides , we have :
2x = 4
divide through by 2
x = 2
substitute x = 2 into equation 1 , that is
y = 2x + 1
y = 2(2) + 1
y = 4 + 1
y = 5
Therefore: x = 2 and y = 5